Analysis of Problems Implementing Online Learning in the Covid-19 Pandemic Period in Biology Learning at SMAN 1 Lingsar - Elmiatun, Elmiatun; Setiadi, Dadi; Sendijadi, Prapti (Journal of Business Social and Technology, 2024)
This study aims to describe the problems faced by grade XI science students during the Covid 19 Pandemic in biology subjects at SMA Negeri 1 Lingsar. The type of research used is descriptive survey research with a qualitative descriptive approach. Data and data sources were obtained directly from research subjects, namely 47 students of grade XI Science 1 and 2. Data collection in research using questionnaire instruments in the form of closed statements. The data analysis technique used is qualitative descriptive analysis with Likert scale. Based on the results of the study, the problems of implementing online learning during the Covid-19 pandemic in biology subjects in class XI Science 2 and 3 at SMAN 1 Lingsar showed problems, namely: related to personal facilities (73.62%), networks (70.64%), economics (69.36%), methods (67.66%), media (67.66%), learning motivation (68.94%), and overloaded tasks (69.36%). The lowest response from students in grade XI Science 2 and 3 in biology subjects at SMAN 1 Lingsar was in the 1st item (44.26%), 4th (49.79%), 8th (65.96%), 9th (61.70%), 11th (61.70%), and 12th (57.87%) with varied answer categories with an average percentage of 52.83%, this shows that this statement indicates that the complex problems faced in the implementation of online learning during the Covid 19 pandemic in biology subjects at SMA Negeri 1 Lingsar, and there needs to be serious handling if you want to return to using the online system. Based on the results of the study, it can be concluded that online learning in biology subjects in class XI Science 2 and 3 has not been carried out well at SMA Negeri 1 Lingsar and there needs to be a review.